Peanuts, popcorn, ice cream, candy, and soda pop, and how they began. - Russell, Solveig Paulson; McDonald, Ralph (Nashville, Abingdon Press, 1970)
Discusses the origin, history, production, and use of peanuts, popcorn, ice cream, candy, and soda pop.
Keywords: Food -- Juvenile literature; Food